The Good Theologian Galileo Galilei - Vesel, Matjaž (Filozofski vestnik, 2016)
The article focuses on Galileo’s understanding of the relationship between revealed and natural truth. In his Letter to Castelli Galileo argued for the separation of theology and natural philosophy. But in the very same letter and in Letter to Dini he appears to use the Bible as a scientific authority, in support of his Copernican views, and thus he seems to contradict his own hermeneutical principles. The author argues that Galileo’s Copernican interpretation of Psalm 18 in Letter to Dini should be understood against the background of Galileo’s argumentation in Letter to Castelli in which Galileo also interpreted a passage from Joshua and that both letters cannot be properly understood without knowledge and understating of the context of their genesis. Galileo’s position is not contradictory but consistent. The second aim of the article is to underline the fact that in these two letters Galileo develops a specific philosophy of nature in order explain his telescopic observations and discoveries on a more fundamental philosophical level.